Entrepreneurial ecosystems in South American most prosperous countries: National and regional level perspectives - Evelyn Calispa; Marcelo Calispa Aguilar; Carlos Serrano Aguiar; Edwin Pozo Safla; Mónica Moreno Barriga; Eduardo García Cabezas; Juan Cayán Martínez (Economies, 2023)
This paper aims to characterise the Entrepreneurial Ecosystems (EE) at the national and regional (subnational) level in Chile, Argentina, and Uruguay employing relevant scientific literature and the latest available data from two well-known entrepreneurial ecosystem indices. Our results show that overall, Chile offers the best national-level ecosystem conditions for productive entrepreneurship among the selected countries. Uruguay and Argentina perform relatively lower than Chile, but they still show potential for improvement by addressing their key system bottlenecks. Moreover, data at the regional level shows that the performance of subnational ecosystems within each country is not homogeneous and regional ecosystems have specific combinations of strengths and weaknesses. Therefore, in a way, these findings confirm the relevance of regional perspectives for research in EE. The data synthesised in this study may be of assistance to researchers interested in understanding entrepreneurship in South American countries and for local policymakers aiming to design context-sensitive entrepreneurship policies.
Keywords: 330; entrepreneurial ecosystems; entrepreneurship; regional development; South America